Exploration of Factors Influencing Maternal Choice Without Medical Indication for Caesarean Section - Misbah Akram, Muhammad Afzal, Zunaira Aziz, Farhat Ijaz, Asim Zia (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The rapid increase of caesarean sections has become the major public health problem. Caesarean section ratio is increasing day by day worldwide without knowing the factors with limited explanation that influence the rising trend without medical indications. Aims: To explore the driving factors which lead to the Caesarean Section and to evaluate the maternal choice without medical indication for Caesarean Section. Methodology: A Phenomenological qualitative approach was used with a semi structured open ended questionnaire. Sample size of ten pregnant women with a third trimester was used in this study. There was an individual in-depth interview with a time duration of 30-40 minutes. Purposive sampling technique was used in this study. Content analysis was done by using the Nvivo-10 software. Result: Participants were recruited from the urban and rural area. Interview session was 30-40 minutes which was convenient to the participant. All the interviews were audio tapes recorded. Interpretative Phenomenological analysis revealed five major themes which are: mother personal beliefs for caesarean section, lack of knowledge to make an informed choice, cultural and social influence, fear of labour pain, non-supportive behaviour of staff and management of health care system were made from these interviews. However, critical knowledge gaps were also observed among study obstetricians, particularly with regards to the indications for and timing of elective caesarean sections. Practical implication: The maternal choice of caesarean section without medical indications and the factors influencing the women decision-making process were complex. Therefore, these findings suggest that healthcare policy makers should attend to the factors that influence maternal choice about caesarean section and promote the normal vaginal birth among women. Conclusion: This study identifies the personal beliefs of mothers are the major factors for taking decisions regarding caesarean section. Furthermore, relative’s consultation with mother’s decision-making become the main influencer to conduct the caesarean section. There is the dire need to involve the relatives during the mother’s antenatal period to support them to make the timely and right decision regarding the mode of birth. Keywords: Caesarean Section, Decision-Making, Influence, Factors, SVD, Pregnant Women